Uzbekistan's Experience in Social Protection - Rustamova, Manzura Rustamovna (Universitas Muhammadiyah Sidoarjo, 2022)
The greatest wealth of the Uzbek state is its hardworking people. In its recent history, independent Uzbekistan has consistently adhered to the principle of strong social protection of the people. This was especially evident during the coronavirus pandemic, which caused a major economic crisis in the world.